2022
DOI: 10.26442/00403660.2022.10.201881
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of <i>Saccharomyces boulardii</i> CNCM I-745 probiotic drug in the prevention and treatment of diarrhea in hospitalized patients with new coronavirus infection COVID-19

Abstract: Aim. To evaluate the efficacy of Saccharomyces boulardii (S. boulardii) CNCM I-745 probiotic drug in preventing and treating diarrhea in hospitalized patients with COVID-19. Materials and methods. A prospective comparative study was conducted in two parallel groups. The study included males and females aged 18 to 60 with the following diagnosis confirmed by polymerase chain reaction: U07.2 Coronavirus infection COVID-19, caused by SARS-CoV-2 virus (grade 13 pneumonia according to CT scan). All patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Through our meta-analysis, the results showed that probiotics could improve the overall symptoms of COVID-19 patients and shorten the duration of symptoms. For gastrointestinal symptoms, the pooled results of five studies ( 22 24 , 29 , 30 ) confirmed that probiotics could obviously reduce the duration of diarrhea in COVID-19 patients. Good consistency exists among the studies, indicating that the results are stable.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Through our meta-analysis, the results showed that probiotics could improve the overall symptoms of COVID-19 patients and shorten the duration of symptoms. For gastrointestinal symptoms, the pooled results of five studies ( 22 24 , 29 , 30 ) confirmed that probiotics could obviously reduce the duration of diarrhea in COVID-19 patients. Good consistency exists among the studies, indicating that the results are stable.…”
Section: Discussionmentioning
confidence: 76%
“…Five studies ( 22 , 25 , 28 , 30 , 31 ) reported the hospital stay (days). A total of 776 patients included, 387 in the probiotics group and 389 in the non-probiotics group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations